PENGARUH PENDEKATAN SAINTIFIK BERBANTUAN MEDIA SMART BOX TERHADAP HASIL BELAJAR IPAS SISWA DI KELAS V SDN 10 SINGKAWANG - Utami, Feby Putri; Sulistri, Emi; Wijaya, Andika Kusuma (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to examine the effect of the scientific learning approach assisted by a smart box media on fifth-grade students’ IPAS learning outcomes in the topic Harmony in Ecosystems at SDN 10 Singkawang. The research employed a quantitative method with a quasi-experimental design, specifically a nonequivalent control group design. The population consisted of all fifth-grade students at SDN 10 Singkawang, with total sampling used to determine the sample. The results of the study show that: (1) there was a significant difference in IPAS learning outcomes between the experimental and control classes, as indicated by the t-test result where tcount (2.6909) > ttable (2.0105); and (2) the scientific learning approach assisted by smart box media had a moderate effect on students’ learning outcomes with an effect size of 0.71. Therefore, it can be concluded that the scientific learning approach assisted by smart box media has a significant and positive impact on the IPAS learning outcomes of fifth-grade students at SDN 10 Singkawang.